AUV ABYSS sensor data (CTD, Fluorometer, turbidity, redox potential) and vehicle performance for dives during RV ALKOR cruise AL532 - Urlaub, Morelia; Lomnitz, Ulrike; Wenzlaff, Emanuel (PANGAEA, 2024)
A total of four missions of the autonomous underwater vehicle (AUV) Abyss was performed end of January 2020 in the Mediterranean Sea around the active deformation zone offshore Etna during RV Alkor cruise AL532. Each dive lasted a few hours and recorded information for a number of sensors including CTD (Seabird SBE49FastCAT), ECO (=combined fluorometer and turbidity sensor; Wetlabs FLNTU/0712017) and REDOX-sensor (Eh-sensor by Ko-Ichi Nakamura from AIST, South Korea). The sensor data is recorded in separate files for each dive. The vehicles performance under water and core functions (roll, pitch, heading, power use, and many others) are recorded in the STATE file of each dive.
Keywords: AUV; AUV ABYSS; AUV underway data; CTD; Redox potential; turbidity